Factors Associated with ARI in Toddlers in Coastal Areas at Kolono and Tumbujaya Health Centers, South Konawe Regency - Soleh, Ahmat; Supodo, Timbul; Sunarsih, Sunarsih (Magister Kesehatan Universitas Mandala Waluya, 2023)
Background: ARI is one of the diseases with a fairly high mortality and mortality rate, the housing environment in particular is very influential on the immune system. Housing that is dirty, cramped, crowded, and does not have adequate clean water facilities will cause children to be often infected by germs that come from dirty places and eventually get various infectious diseases. Houses that do not have enough clean air flow and whose residents are often found in the kitchen accumulated in the house will be susceptible to ARI. Methods: The type of research uses a quantitative research design with a cross sectional study design with a total sample of 95 respondents. Results: There is a relationship between residential density, home environment and immunization with the incidence of ARI in children under five in the coastal area of ​​the working area of ​​the Kolono Health Center and Tumbujaya Health Center, Kolono District and East Kolono District, South Konawe Regency. Conclusion: Factors related to ARI in toddlers include residential density, home environment, and immunization.